DESIGN OF A 5000 KL CRUDE PALM OIL (CPO) TANK WITH STEEL PLATES - Atmadja, Gilbert Laurent; Sutandar, Erwin; Aryanto, Aryanto (Fakultas Teknik Universitas Tanjungpura, 2024)
The study is centered on designing a 5000 KL Crude Palm Oil (CPO) Tank within Indonesia's palm oil industry, ensuring adherence to the API 650 13th Edition standard to effectively withstand operational and environmental loads. Plate theory, specifically the Kirchoff-Love theory, is employed to model structural components such as annular, shell, and roof plates, which must endure various loads including dead, internal (hydrostatic and pressure), external (wind, pressure, snow), live, and seismic loads as specified by API guidelines. Stress analysis is conducted to ensure compliance with material limits, utilizing ASTM A573M Grade 485 steel for plates and standard compressive strength for foundations.The research involves detailed phases encompassing data collection, preliminary design, structural modeling, loading analysis, stress assessment, weld design, and foundation planning utilizing SAP2000 software. Calculated stresses on tank plates remain well below API limits, confirming structural robustness. Welding details for butt and corner joints are carefully planned for durability, while deep pilings and pile caps provide stability against ground movements.By integrating empirical data and theoretical calculations, the study presents a comprehensive plan for constructing a dependable and cost-effective palm oil storage facility, thereby enhancing safety and efficiency within Indonesia's palm oil sector.